Open Educational Resources to Improve Students’ Learning & Performance: A Case Study with Practitioner’s Approach (International Conference on Computers in Education, 2016)
Technology continues to play a pivotal role in every field. With each passing day, technology has gained an exponential prominence in the field of education. This paper attempts to survey the open educational resources along with their unique and major role across several educational sectors. A study is conducted to launch open educational resources using freely available resources, followed by active learning conduction. Then an analysis is carried out by authors related to the usage of open educational resources (OER) with respect to the performance of the students. Finally, a conclusion is derived regarding the impact of OER on the learning and performance of students